Anything is possible ebook A novel. - Strout, Elizabeth (2017)
NEW YORK TIMES BESTSELLER • An unforgettable cast of small-town characters copes with love and loss in this “compulsively readable” ( San Francisco Chronicle ) novel from the Pulitzer Prize–winning author of Olive Kitteridge and My Name is Lucy Barton “This book, this writer, are magnificent.”—Ann Patchett WINNER OF THE STORY PRIZE • A BEST BOOK OF THE YEAR: The New York Times, The Washington Post, USA Today, People, NPR, Entertainment Weekly, Newsday, The Seattle Times, Esquire, The Guardian, Kirkus Reviews, Publishers Weekly In Anything Is Possible, Elizabeth Strout explores the whole range of human emotion through the intimate dramas of people struggling to understand themselves and others. Here are two sisters: One trades self-respect for a wealthy husband while the other finds in the pages of a book a kindred spirit who changes her life. A grown daughter longs for mother love even as she comes to accept her mother’s happiness in a foreign country. And Lucy Barton returns to visit her siblings after seventeen years of absence.    Reverberating with the deep bonds of family, and the hope that comes with reconciliation, Anything Is Possible “confirms Strout as one of our most grace-filled, and graceful, writers” ( The Boston Globe ).